E-Modules with Realistic Mathematics Education (PMR) Approach to Improve Students’ Mathematical Problem Solving Skills - Heldawati, Heldawati; Yulianti, Dwi; Nurhanurawati, Nurhanurawati; Nurwahidin, Muhammad; Sutiarso, Sugeng (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2024)
This study aims to develop e-modules of mathematics learning with Realistic Mathematics Education (PMR) approach to improve students’ concept understanding and problem solving skills on the material of rows and series. The method used includes making a framework, preparing e-modules, and evaluating products based on suggestions from validators and students. The development results show that this e-module consists of various important components such as concept maps, instructions for use, and activity sheets designed to facilitate active learning. The evaluation shows that the use of e-modules can increase students’ motivation and understanding of mathematics materials, as well as help them in applying mathematical concepts in the context of daily life. This research emphasizes the importance of innovation in mathematics learning to create a more meaningful and effective learning experience for students